Bipolar resistive switching on Ti/TiO2/NiCr memory cells (Superficies y Vacío, 2017)
We investigated the electric-field-induced resistance-switching behavior of metal-insulator-metal (MIM) cells based on TiO2 thin films fabricated by the reactive RF-sputtering technique. MIM cells were constructed by sandwiched TiO2 thin films between a pair of electrodes; Ti thin films were employed to form an ohmic bottom contact and NiCr thin films were employed to form Schottky top electrodes obtaining Ti/TiO2/NiCr MIM cells. Schottky barrier height for the TiO2/NiCr junction was determined according to the thermionic emission model by using the Cheung´s functions. SEM and Raman analysis of the TiO2 thin films were carried out to ensure the quality of the films. Current-Voltage (I-V) sweeps obtained at room temperature by the application of dc bias showed a bipolar resistive switching behavior on the cells. Both low resistance state (ON state) and high resistance state (OFF state), of Ti/TiO2/NiCr cells are stable and reproducible during a successive resistive switching. The resistance ratio of ON and OFF state is over 103 and the retention properties of both states are very stable after 105 s with a voltage test of 0.1 V.